Neutralidad, diversidad y celebración de las festividades religiosas en la escuela pública (Stato, Chiese e pluralismo confessionale, 2018)
SUMARIO: 1. Introducción - 2. Libertad religiosa y celebración de las festividades religiosas - 3. La neutralidad ideológico-religiosa de los centros educativos públicos - 4. Celebración de festividades religiosas en la escuela de titularidad pública - 4.1. Celebración de festividades que presentan un significado religioso y una tradición cultural - 4.2. La respuesta de los Tribunales de Justicia en materia de celebraciones religiosas - 4.3. Algunas claves para la solución de estos conflictos - 5. Celebración de las festividades religiosas en el horario escolar - 5.1. Marco jurídico de las festividades en el ámbito escolar - 5.2.  Discriminación de los grupos religiosos minoritarios - 6. Consideraciones finales: la acomodación razonable de las creencias religiosas.Neutrality, diversity and celebration of religious festivities in public schoolsAbstract: This paper analyzes some legal conflicts derived from the celebration of religious festivities in the public school. On the one hand, the celebration of certain festivals that, while showing a cultural tradition, at the same time, present a religious meaning, mainly of Christian inspiration. On the other, when permission is requested to celebrate and commemorate such festivities during school hours. Beyond the concrete problem, it is important to start from the position of inclusive neutrality that public authorities must adopt to manage the religious diversity that manifests itself in this specific area and which, in turn, is the best way to guarantee the right of parents to choose the education they wish for their children.